2022
DOI: 10.1186/s12893-022-01782-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal reinforcement with barbed suture is associated with low anastomotic leakage rates after laparoscopic low anterior resection for rectal cancer: a retrospective study

Abstract: Background Anastomotic leakage (AL) is one of most severe postoperative complications following low anterior resection (LAR) for rectal cancer, and has an adverse impact on postoperative recovery. The occurence of AL is associated with several factors, while few studies explored the role of intracorporeal barbed suture reinforcement in it. Methods Consecutive cases underwent laparoscopic LAR for rectal cancer from Mar. 2018 to Feb. 2021 in our cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The current studies have confirmed that tumor size, distance from the tumor to the anal verge, and the use of reinforcement sutures to the anastomosis are independent risk factors for symptomatic AL (29). Lin et al (11) conducted a retrospective study of 292 patients undergoing laparoscopic low anterior resection for rectal cancer. They found that the use of barbed sutures for anastomotic reinforcement was associated with a low incidence of AL.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The current studies have confirmed that tumor size, distance from the tumor to the anal verge, and the use of reinforcement sutures to the anastomosis are independent risk factors for symptomatic AL (29). Lin et al (11) conducted a retrospective study of 292 patients undergoing laparoscopic low anterior resection for rectal cancer. They found that the use of barbed sutures for anastomotic reinforcement was associated with a low incidence of AL.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, Senagore et al (10) have concluded that reinforcement of colorectal anastomoses with bioabsorbable material did not affect the incidence of anastomotic leaks but may reduce anastomotic strictures. However, Lin et al (11), in a study of anastomotic reinforcement with barbed sutures during laparoscopic low anterior resection of rectal cancer, found that the incidence of AL was 10% in the control group and 2.82% in the suture-reinforced group, suggesting that reinforcement of the anastomotic "dog's ear" area with sutures is associated with a low incidence of AL. Similarly, Ban et al (12) have demonstrated that reinforcement of the anastomosis with barbed sutures after laparoscopic rectal cancer resection significantly reduced the incidence of AL.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 27 full-text were excluded, 19 studies were excluded because they were single-arm studies, and eight studies did not provide data information because they were clinical guidelines. Fourteen studies met the inclusion criteria for this analysis (12 retrospective studies (11,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) versus two randomized controlled studies (26,27)). A total of 14 studies (11,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) with 2,452 patients (reinforced suture group, n = 1196, and non-reinforced suture group, n = 1,256) were included.…”
Section: Study Detailsmentioning
confidence: 99%
“…Fourteen studies met the inclusion criteria for this analysis (12 retrospective studies (11,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) versus two randomized controlled studies (26,27)). A total of 14 studies (11,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) with 2,452 patients (reinforced suture group, n = 1196, and non-reinforced suture group, n = 1,256) were included. All patients included in the study underwent rectal resection.…”
Section: Study Detailsmentioning
confidence: 99%
See 1 more Smart Citation